Immune Tolerance vs. Immune Resistance: The Interaction Between Host and Pathogens in Infectious Diseases - Ahmad, Hafiz Ishfaq; Jabbar, Abdul; Mushtaq, Nadia; Javed, Zainab; Hayyat, Muhammad Umar; Bashir, Javaria; Naseeb, Iqra; Abideen, Zain Ul; Ahmad, Nisar; Chen, Jinping (Frontiers in Veterinary Science, 2022)
The immune system is most likely developed to reduce the harmful impact of infections on the host homeostasis. This defense approach is based on the coordinated activity of innate and adaptive immune system components, which detect and target infections for containment, killing, or expulsion by the body's defense mechanisms. These immunological processes are responsible for decreasing the pathogen burden of an infected host to maintain homeostasis that is considered to be infection resistance. Immune-driven resistance to infection is connected with a second, and probably more important, defensive mechanism: it helps to minimize the amount of dysfunction imposed on host parenchymal tissues during infection without having a direct adverse effect on pathogens. Disease tolerance is a defensive approach that relies on tissue damage control systems to prevent infections from causing harm to the host. It also uncouples immune-driven resistance mechanisms from immunopathology and disease, allowing the body to fight infection more effectively. This review discussed the cellular and molecular processes that build disease tolerance to infection and the implications of innate immunity on those systems. In addition, we discuss how symbiotic relationships with microbes and their control by particular components of innate and adaptive immunity alter disease tolerance to infection.